Green Synthesis of High Temperature Stable Anatase Titanium Dioxide Nanoparticles Using Gum Kondagogu: Characterization and Solar Driven Photocatalytic Degradation of Organic Dye - K S, Saranya; Vellora Thekkae Padil, Vinod; Senan, Chandra; Pilankatta, Rajendra; K, Saranya; George, Bini; Wacławek, Stanisław; Černík, Miroslav (Nanomaterials (Basel, Switzerland), 2018)
The present study reports a green and sustainable method for the synthesis of titanium dioxide (TiO₂) nanoparticles (NPs) from titanium oxysulfate solution using Kondagogu gum (Cochlospermum gossypium), a carbohydrate polymer, as the NPs formation agent. The synthesized TiO₂ NPs were categorized by techniques such as X-Ray Diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy analysis, Raman spectroscopy, scanning electron microscope- Energy-dispersive X-ray spectroscopy (SEM-EDX), Transmission electron microscopy (TEM), High-resolution transmission electron microscopy (HR-TEM), UV-visible spectroscopy, Brunauer-Emmett-Teller (BET) surface area and particle size analysis. Additionally, the photocatalytic actions of TiO₂ NPs were assessed with regard to their ability to degrade an organic dye (methylene blue) from aqueous solution in the presence of solar light. Various parameters affecting the photocatalytic activity of the TiO₂ NPs were examined, including catalyst loading, reaction time, pH value and calcination temperature of the aforementioned particles. This green synthesis method involving TiO₂ NPs explores the advantages of inexpensive and non-toxic precursors, the TiO₂ NPs themselves exhibiting excellent photocatalytic activity against dye molecules.
Keywords: photocatalysis; green synthesis; titanium dioxide nanoparticles; methylene blue; gum kondagogu